New formulation of reduction factors for pile groups under lateral loading through Model Tree technique. (25th November 2020) - Khoshroo, Reza; Derakhshani, Ali
ABSTRACT: Under lateral loading, the p-y curves of a pile group differ from those of a single pile due to group effects. Hence, p-y curves of single piles are modified by reduction factors for either a row or a group of piles. In order to improve the available approaches for estimation of reduction factors, a database was compiled from the experimental test results reported in the literature. Accordingly, a robust machine learning technique i.e. the M5' Model Tree method was used to propose new formulas for prediction of row and group reduction factors for pile groups. The new relationships are simple, physically sound and accurate based on different statistical measures. These also account for additional parameters of soil properties that affect the reduction factors. The new models compare favorably with recommendations of design guidelines. Furthermore, considering different levels of risks, appropriate safety factors that can be useful for engineers are presented.